The value of pre-transplant coronary angiography findings in kidney transplant candidates at high risk for cardiovascular disease - Morená, Leela; Al Jurdi, Ayman; Adam, Eduardo Leal; Verhoeff, Rucháma; Palsson, Ragnar; Ribas, Guilherme Taborda; Hullekes, Frank; Cohen Bucay, Abraham; Elias, Nahel; Riella, Leonardo. V. (Frontiers in Transplantation, 2023)
Introduction: Cardiovascular disease is a significant cause of mortality after kidney transplantation. Whether pre-transplant screening for coronary artery disease (CAD) in asymptomatic kidney transplant candidates (KTCs) is beneficial is unclear. Methods: We conducted a retrospective cohort study evaluating post-transplant cardiovascular events in 192 high-risk KTCs who underwent pre-transplant CAD evaluation. The study aimed to identify risk factors associated with finding severe CAD on pre-transplant angiography, and to assess the relationship between screening strategies and post-transplant cardiovascular events. Results: At five years post-transplant, cardiovascular events occurred in 23.9% of subjects. Prior CAD history and left ventricular ejection fraction (LVEF) <50% were associated with higher odds of finding severe CAD on pre-transplant angiography. Severe CAD on angiography was associated with a higher risk of early cardiovascular events within six months of transplantation. However, coronary intervention in KTCs with severe CAD was not associated with lower rates of post-transplant cardiovascular events. Conclusion: Pre-transplant coronary angiography to identify severe CAD is of highest yield in KTCs with a history of CAD or an LVEF <50%. Our findings indicate that the identification of severe CAD in KTCs has prognostic significance for the early post-transplant period. Optimization of medical therapy in these high-risk KTCs may improve post-transplant cardiovascular outcomes.